Development of Hybrid Model From CCR-I and SBM-I for Measuring Mix Efficiency Level - Asbullah, Muhammad Asyraf (2010)
In today’s world, Data Envelopment Analysis (DEA) has been used widely in manyareas of efficiency analysis study. Basically, the DEA method has two different types of measurement, which called as radial and non-radial measure. Both measures were represented by the input orientated model of Charnes-Cooper-Rhodes (CCR-I) and Slack-based Measure (SBM-I). Problems that arise from CCR-I model are due to its excessive two phase’s procedure, unreported of nonzero slacks along its efficiency score and the terminology of weak efficiency. The shortcomings of SBM-I are because the proportionality aspect was avoided and all inefficiencies are reported only in a single score. Furthermore, the requirement to solve two different models simultaneously in order to determine the mix level seems demanding. This study aims to overcome the mentioned shortcomings by proposing a new single DEA model. We also wish to combine the characteristics of both CCR-I and SBM-I in this model. In addition, the proposed model is targeting to derive a new technique for mix efficiency evaluation. This model and technique was illustrated using existing data sets. We observed that the results from this new model reflecting the nonzero slacks in its optimal score and remove the weak efficiency terminology. We have discovered that the corresponding characteristics of CCR-I and SBM-I was delineated and the mix level of the new technique is comparable with the results obtained from the standard method. As conclusion, the findings of this study contributes to reduce the computational efforts, provides a simple way to determine the mix efficiency levels and successfully combining the radial and non-radial characteristics in a single DEA model.